Anisotropic ion transport in 2D polymer single crystal-based solid polymer electrolytes. (June 2020) - Cheng, Shan; Li, Xiaowei; Zheng, Yongwei; Smith, Derrick M.; Li, Christopher Y.
Abstract: Solid polymer electrolytes (SPEs) are promising for the next-generation all-solid-state lithium metal battery (LMB) applications. The effect of semicrystalline structure on ion transport is two-fold: the crystalline domains provide a tortuous diffusion pathway (structural effect) while the tethered chains can cause sluggish ion diffusion (dynamic effect). These two effects are intertwining in a bulk semicrystalline SPE system. In this work, we fabricate a series of polymer single crystal (PSC)-based SPEs by infiltrating lithium bis(trifluoromethylsulfonyl) imide (LiTFSI) into poly(ethylene oxide) (PEO) PSC films. The obtained SPE films show anisotropic conducting behavior with the in-plane conductivity being one to three orders of magnitudes greater than the through-plane conductivity, which can be attributed to the PSC-guided ion transport. The room temperature in-plane conductivity of the PSC SPE can be comparable to its amorphous counterpart, indicating that the tortuosity effect plays a major role in the reduced ionic conductivity of semicrystalline SPEs. PSC-LiTFSI superstructure is observed in the PSC SPEs due to selective perforation of the crystalline PEO lamellae by LiTFSI salts. This work demonstrates the importance of the crystalline morphology on the ion transport in semicrystalline SPEs. Graphical abstract: Image, graphical abstract